The Maritime Smuggling Project: Challenges Within Collaborative Maritime Policing in The Netherlands - Mauro Boelens; Yarin Eski; Danique De Rijk (Ocean and Society)
The Netherlands hosts a significant drug industry involving global crime groups targeting local professionals, such as fishers for drug smuggling, real estate agents for money laundering, and harbor masters for marina access. To raise awareness of potential criminal involvement, various government organizations collaborate within an Organized Crime Field Lab. This approach shifts the focus from repressively apprehending criminals to protecting legal businesses and professionals by enabling the public to inform, detect, and report smuggling activities, and by helping relevant sectors identify and regulate activities that facilitate organized crime. This article examines how maritime policing professionals experience the process, outcomes, and challenges within the Maritime Smuggling Project (MSP) and its contribution to building a more resilient society against criminal involvement. Based on 34 interviews, hybrid observations, and an online questionnaire with MSP participants, the study suggests that maritime criminal justice relies on the idea that a resilient community is less likely to engage in or facilitate criminal maritime activities. However, it also indicates that collaboration in itself is not enough to create an impact on policing. Findings reveal that innovations in criminal justice need open‐ended, long‐term, impact‐focused responses from projects like the MSP, along with maritime professionals willing to adopt new policing methods. Yet, traditional, path‐dependent criminal justice institutions often undermine these innovations by prioritizing immediate, measurable, short‐term results that benefit their organization instead of the overarching goal of preventing maritime crime and societal involvement in it. As a result, even those tasked with developing innovative approaches are limited by institutional constraints and ingrained habits.